Faktor Penyebab dan Penanggulangan Pelanggaran Izin Trayek di Kabupaten Manggarai - Maria Anne Febriani Tambuk; Sukardan Aloysius; Darius Mauritsius (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this research is to analyse the factors causing and overcoming violations of route permits in Manggarai Regency. This research is an empirical juridical research, which uses primary data sources, namely field research with interview methods to sources with an interest in this paper and secondary. Based on the results of the research, the factors causing violations of route permits by the Department of Transportation of Manggarai Regency are divided into three, namely government factors, namely the lack of honorary staff in the terminal; vehicle business factors (owners and drivers) caused by economic factors, administrative factors, intense competition between transport drivers; community factors that do not obey government regulations. Countermeasures are supervision and inspection by means of routine supervision and inspection, sudden and quarterly inspections; granting permits with special conditions, monitoring and evaluation; permit scoping. Law enforcement is preventive and repressive.